Upaya Menanamkan Moderasi Beragama Kepada Mahasiswa PAI Melalui Kegiatan Pamong Santri Mahasiswa (PASMA) di Universitas Tidar - Mohammad 'Ulyan; Umi Rachmawati (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2024)
The issue of radicalism and intolerance in educational institutions has become a phenomenon that is widely seen, not least on Public Higher Education (PTU) campuses. It has become a hot theme and a particular concern for all groups, such as academics, religious scholars, the general public and even the central government. as well as regional. The aim of this research is to find out the extent of the role of the Student Santri Teachers (PASMA) in instilling the value of moderation in students. The method in this research uses qualitative research, which is a research process that produces descriptive data in the form of written and spoken words from the people and actors observed. The result of this research is that the Student Santri Community Service (PASMA) activity aims to provide students with religious provisions. PASMA activities are carried out through group methods and moving classes where each Pamong provides material in different classes with the same material. Through this activity, it is hoped that students will have a deep and moderate understanding of religion.